Computer Networks as Tools for Enlarging Social Networks in Western Civilization. - Michalec, Kaja; Lilien, Leszek (Comparative Civilizations Review)
The full text of a position paper on “Computer Networks as Tools for Enlarging Social Networks in Western Civilization” is presented. The paper aims to analyze the history and the present day of computer-based support for social networking.